A chronology of climatic downturns through the mid- and late-Holocene : tracing the distant effects of explosive eruptions from palaeoclimatic and historical evidence in northern Europe - Helama, Samuli; Holopainen, Jari; Macias-Fauria, Marc; Timonen, Mauri; Mielikäinen, Kari (Polar Research, 2016)
Peer reviewed